2018
DOI: 10.1016/j.tetlet.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Recent topics of the stereodivergent synthesis of natural products

Abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…To complement, these bond forming processes, geometric isomerization provides a platform to invert configuration at the desired stage of a synthesis. This has obvious implications for stereodivergent synthesis campaigns. , An exemplar of alkene configuration manifesting itself in biological efficacy is the marine polyketide (+)-discodermolide 342 , where the Z -configured olefin is vital to ensure effective microtubule stabilizing ability (Scheme ). Similarly, the signature Z -configured alkene in prostaglandins, such as prostaglandine F 2α 343 , further underscores the importance of 2D-stereocontrol in structure–function interplay.…”
Section: Energy Transfer-enabled Alkene Isomerization Applied To Tota...mentioning
confidence: 99%
“…To complement, these bond forming processes, geometric isomerization provides a platform to invert configuration at the desired stage of a synthesis. This has obvious implications for stereodivergent synthesis campaigns. , An exemplar of alkene configuration manifesting itself in biological efficacy is the marine polyketide (+)-discodermolide 342 , where the Z -configured olefin is vital to ensure effective microtubule stabilizing ability (Scheme ). Similarly, the signature Z -configured alkene in prostaglandins, such as prostaglandine F 2α 343 , further underscores the importance of 2D-stereocontrol in structure–function interplay.…”
Section: Energy Transfer-enabled Alkene Isomerization Applied To Tota...mentioning
confidence: 99%
“…Indeed, synthesis and stereochemical assessment of such compound libraries often require experimental excellence comparable to that of natural product total syntheses, especially if preparation of pure enantiomers is considered. 12 At the same time, reported studies cited above, and those that followed [13][14][15][16][17][18] demonstrated utility and efficiency of this strategy, justifying the design of new libraries realizing the strategy and development of practical synthetic approaches to them. Therefore, we set the goal to develop efficient and practical synthetic routes to libraries of the conformationally restricted probes, and report herein our results in synthesis of conformationally restricted analogs of L-glutamic acid (Glu), known as an important excitatory neurotransmitter in the central nervous system, 19,20 as well as the substrate of the glutamate racemase, potential target for a new generation of antibiotics.…”
Section: Introductionmentioning
confidence: 89%
“…Recently, stereodivergent catalysis has emerged as aviable approach to address this problem. [3,4] Traditional asymmetric catalysis mainly focuses on introducing chirality to prochiral substrates using chiral catalysts.W hile this strategy can effectively generate one stereoisomer of chiral molecules bearing multiple stereogenic centers (or multiple stereochemical elements), stereochemically controlled synthesis of the complementary diastereomer(s) is often difficult. By contrast, stereodivergent reactions could permit the access to any stereoisomer of chiral molecules that possess multiple stereochemical elements.B yu sing different combination of enantiomers of chiral catalysts and reagents,all stereoisomers can be obtained selectively.Such aprocess holds aparticular value in natural product chemistry and medicinal chemistry, where the capability to access all the stereoisomers is of great importance to structure elucidation and structure-activity relationship studies.T herefore,t he development of catalytic stereodivergent transformations that allows for stereocontrolled synthesis of different stereoisomers of chiral molecules is highly desirable.…”
Section: Introductionmentioning
confidence: 99%